2011
DOI: 10.1080/0163853x.2011.582348
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Study: A Situation Model Analysis of Reading Times

Abstract: One of the basic findings on situation models and language comprehension is that reading times are affected by the changing event structure in a text. However, many studies have traditionally used multiple, relatively short texts, in which there is little event consistency across the texts. It is unclear to what extent such changes will be observed when readers are given a longer, more coherent text, such as a novel. The current study discovered that while some of the characteristics of language comprehension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 23 publications
(43 reference statements)
0
38
0
Order By: Relevance
“…Several studies have found increased reading times accompanying temporal shifts (Radvansky & Copeland, 2010;Radvansky et al, 2001;Rinck & Weber, 2003;Zwaan, Magliano, et al, 1995;. However, other studies have found decreases in reading times for historical texts (Radvansky et al, 2001) and in a novel (McNerney et al, 2011).…”
Section: Abstract Situation Models Memory Readingmentioning
confidence: 90%
See 4 more Smart Citations
“…Several studies have found increased reading times accompanying temporal shifts (Radvansky & Copeland, 2010;Radvansky et al, 2001;Rinck & Weber, 2003;Zwaan, Magliano, et al, 1995;. However, other studies have found decreases in reading times for historical texts (Radvansky et al, 2001) and in a novel (McNerney et al, 2011).…”
Section: Abstract Situation Models Memory Readingmentioning
confidence: 90%
“…For example, when a story has been centered on John and the narrator begins describing events involving Julia. Generally, shifts along this dimension result in an increase in reading time (McNerney et al, 2011;Rinck & Weber, 2003;, although not exclusively. In at least one case, it led to significantly faster reading times (Radvansky et al, 2001, Exp.…”
Section: Abstract Situation Models Memory Readingmentioning
confidence: 99%
See 3 more Smart Citations